The role of phagosomal pH on the size-dependent efficiency of cross-presentation by dendritic cells - Tran, Kenny K. (2008)
Vaccines able to stimulate CD8(+)T cells are crucial in controlling a broad range of infectious diseases and tumors. To induce effective CD8(+)T cell responses, exogenous antigen has to be cross-presented onto major histocompatibility complex (MHC) class I molecules by dendritic cells. Although particle size has been recognized as a critical factor of vaccine design, it is unclear how the size of vaccine carriers impacts the intracellular processing of exogenous antigen and cross-presentation onto MHC class I molecules. In this study, by using polystyrene beads with narrowly defined sizes as model antigen carriers, we demonstrate that particle size mediates the efficiency of cross-presentation of exogenous antigens. By examining the intracellular trafficking, kinetics of phagosomal pH and degradation of antigens bounded to beads, we illustrate the possible mechanisms attributed to the profound effect of particle size on the efficiency of cross-presentation. Antigen bounded to 50 nm beads was shuttled rapidly to an acidic environment within half an hour post-exposure to cells, leading to its rapid and unregulated degradation and inefficient cross-presentation. In contrast, antigen bounded to 500 nm and 3 μm beads remained in a more neutral environment, which preserved the majority of antigens, leaving it available for the generation of peptides to be loaded onto MHC class I molecules. We conclude that the size of antigen carriers plays a critical role in directing antigen to the class I antigen presentation pathway. Our results, together with previous in vivo studies on the effect of particle size on CD8(+)T cell responses, provide insight into the rational design of vaccines for the stimulation of cell-mediated immunity.